The Rise of the Diva on the Sixteenth-Century Commedia dell'Arte Stage - Kerr, Rosalind, 1941- (Book collections on Project MUSE., 2015)
The Rise of the Diva on the Sixteenth-Century Commedia dell'Arte Stage examines the emergence of the professional actress from the 1560s onwards in Italy.